Catalysis for Alternative Energy Generation - Guczi, László (Springer New York, 2012)
The increase of greenhouse gases in the atmosphere and the decrease of the available amount of fossil fuels necessitate finding new alternative and sustainable energy sources in the near future. This book summarizes the role and the possibilities of catalysis in the production of new energy carriers and in the utilization of different energy sources. The main goal of this work is to go beyond those results discussed in recent literature by identifying new developments that may lead to breakthroughs in the production of alternative energy. The book discusses the use of biomass or biomass derived materials as energy sources, hydrogen formation in methanol and ethanol reforming, biodiesel production, and the utilization of biogases. Separate sections also deal with fuel cells, photocatalysis, and solar cells, which are all promising processes for energy production that depend heavily on catalysts.